2003
DOI: 10.1103/physreve.67.046617
|View full text |Cite
|
Sign up to set email alerts
|

Exact soliton solutions of coupled nonlinear Schrödinger equations: Shape-changing collisions, logic gates, and partially coherent solitons

Abstract: The different dynamical features underlying soliton interactions in coupled nonlinear Schrödinger equations, which model multimode wave propagation under varied physical situations in nonlinear optics, are studied. In this paper, by explicitly constructing multisoliton solutions (up to four-soliton solutions) for two-coupled and arbitrary N-coupled nonlinear Schrödinger equations using the Hirota bilinearization method, we bring out clearly the various features underlying the fascinating shape changing (intens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
182
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(192 citation statements)
references
References 23 publications
6
182
1
Order By: Relevance
“…Later, Radhakrishnan et al have shown that the solitons in the Manakov system (1) exhibit certain novel inelastic (energy sharing) collisions [11] in contrast to single component NLS system. Kanna et al, have obtained the multisoliton solutions for the multicomponent Manakov system (2) using the Hirota's method [15]. Thus the system has been well studied in the literature [8,11,[13][14][15][16] and the existence of N -soliton (for arbitrary N ) solution and also its proof has been obtained.…”
Section: Soliton Collisions In the Icnls (Manakov) System: Type-i Enementioning
confidence: 99%
See 4 more Smart Citations
“…Later, Radhakrishnan et al have shown that the solitons in the Manakov system (1) exhibit certain novel inelastic (energy sharing) collisions [11] in contrast to single component NLS system. Kanna et al, have obtained the multisoliton solutions for the multicomponent Manakov system (2) using the Hirota's method [15]. Thus the system has been well studied in the literature [8,11,[13][14][15][16] and the existence of N -soliton (for arbitrary N ) solution and also its proof has been obtained.…”
Section: Soliton Collisions In the Icnls (Manakov) System: Type-i Enementioning
confidence: 99%
“…Kanna et al, have obtained the multisoliton solutions for the multicomponent Manakov system (2) using the Hirota's method [15]. Thus the system has been well studied in the literature [8,11,[13][14][15][16] and the existence of N -soliton (for arbitrary N ) solution and also its proof has been obtained. In this section, we restrict our review to the interaction of two solitons in the Manakov system.…”
Section: Soliton Collisions In the Icnls (Manakov) System: Type-i Enementioning
confidence: 99%
See 3 more Smart Citations